Trejo's cantina : cocktails, snacks & amazing nonalcoholic drinks from the heart of Hollywood - Trejo, Danny, 1944- (Clarkson Potter/Publishers, 2023)
"A cantina-style celebration of Mexican food and drink, entertaining, and Hollywood culture in 100 recipes for nachos, tacos, and Danger Dogs plus cocktails and non-alcoholic drinks from the legendary actor, restaurateur, and author of the acclaimed Trejo's Tacos The cantina is the place where families, friends, and colleagues gather to celebrate. In Trejo's Cantina, beloved actor and restaurateur Danny Trejo shares recipes for snacks and drinks that celebrate his traditions and spirit. Along with mouthwatering recipes that make all people feel welcome, from plant-based (Vegan Tamales) and vegetarian (Fight Night Nachos; Mexican Grilled Caesar) to meaty faves (Chorizo Smash Burgers; Tijuana-Style Birria), there are also dozens of inventive takes on classic cocktails including spicy Margaritas and Oaxacan "Moscow" Mules as well as dozens of thirst-quenching non-alcoholic drinks such as Agua Frescas (Pineapple, Guava Lime, Mango), a Tamarind Fizz, and a Cacao Chile Smoothie. Danny includes helpful tips like how to build a booze-free bar, how to master the tamale, how to mix-and-match salsas, and much more. He also reminisces about his upbringing in Los Angeles, from barhopping with uncles on Olvera Street to his memories of sneaking into movie theaters to cool off and watching films wide-eyed and inspired. Danny's approach to entertaining is accessible, celebratory, and empowering to cooks of all skill levels. Trejo's Cantina, at its heart, is about living to the fullest, and about how no matter what happens, you need to eat well, drink with gratitude, and celebrate life"--